Flexographic printing of nanoparticulate tin-doped indium oxide inks on PET foils and glass substrates - Wegener, Carsten Moritz; Spiehl, Dieter; Sauer, Hans Martin; Mikschl, Florian; Liu, Xinxin; Kölpin, Nadja; Schmidt, Michael; Jank, Michael; Dörsam, Edgar; Roosen, Andreas (Journal of Materials Science, 2016)
This contribution deals with flexographic printing of nanoparticulate tin-doped indium oxide (ITO) inks for the manufacture of fine lines on PET foils and glass substrates. The development and optimization of ITO inks, based on solutions of water and ethanol, for the flexographic printing process is presented. The influence of the solvent composition, of the particle content, and of the molar mass of the binder polyvinylpyrrolidone on the printing result is shown. ITO lines with a minimum line width of around 120 µm were printed using a printing plate with a feature size of 50 µm; the ITO lines exhibited a thickness of around 1 µm. Laser post-treatment was used to consolidate the top layer of the nanoparticulate ITO structures resulting in improved electrical properties; low sheet resistance values of around 300 Ω/□ were achieve